A study of preferred and natural memory colours across different ethnic groups. Issue 2 (9th January 2023) - Cao, Mingkai; Luo, Ming Ronnier; Lu, Yan; Xaio, Kaida
Abstract: A psychophysical experiment was carried out to specify the preferred and natural memory colours corresponding to 24 familiar objects on mobile displays. These objects were selected to cover a large colour gamut in CIELAB space. One hundred and six observers from five different ethnic groups participated. Forty‐nine colours for each object were rendered three‐dimensionally to cover a large colour range. The results showed inter‐observer variations are small between different ethnic groups, about 1.4 and 1.3 CIEDE2000 colour difference units for naturalness and preference, respectively. Comparing the preference and the naturalness colour centres, the preferred colours are brighter and more colourful than naturalness colours, by 1 and 2 units in L * and C *ab attributes, respectively. Both sets of data show a great hue consistency. The results showed that different ethnic groups agreed well on the objects studied. It was found that the best‐agreed objects are strawberry, green apple, tomato, corn and purple grape, and the worst‐agreed objects are blueberry, broccoli, smurf, green pepper and blue sky.